ICE GRADING EQUIPMENT - EXPERIMENTAL ICE DOZER FOR PIONEERING IN ROUGH ICE. - Gifford, Sidney E. (1965)
Much of the polar regions are covered with annual and perenial sea ice. Operations often necessitate using this ice for campsites, roads, runways, and other facilities, but seldom is it suitable for such installations without some preparation. Removal of hummocks, pressure ridges and other natural obstructions present particular problems. This technical note covers the development of an experimental ice dozer for pioneering rough ice areas. It consists of a rotating, spiked-tooth cutter mounted on the front of a crawler tractor. This unit, designated as an ice dozer, was functionally tested at Port Hueneme, California, and Devil's Lake, North Dakota. It exhibited good ice cutting characteristics, but lacked sufficient control for level cutting. It was modified for improved control in 1964 and shipped to McMurdo, Antarctica for field testing during the summer season of Deep Freeze 66. (Author)